An economic comparison of forest recreation, timber and carbon fixing values with agriculture in Wales: a geographical information systems approach - Bateman, Ian J. (1996)
The research examines the financial and economic viability of transferring land presently under agricultural use into multipurpose farm-forestry in Wales. Three woodland benefit streams are examined in detail: the value of open-access recreation; the production of timber and; the net carbon storage generated by afforestation. Modelling of the spatial variability determining the production of these benefits is enhanced by the novel application of a geographical information system(GIS). Monetary evaluation of non-market recreation benefits is achieved by reference to both the contingent valuation and travel cost methods with prior studies being reviewed and new work presented. By contrast carbon storage benefits are valued purely by reference to the existing literature. Both of these analyses yield social values whereas our study of timber production produces both shadow and market valuations.